Escola, violência e trabalho infantil no Brasil - Whitaker, Dulce C. A. [UNESP] (Universidade Estadual Paulista (Unesp), 1989)
Este artigo é um ensaio de interpretação que busca explicar a violência contra crianças em nosso País a partir de alguns resultados da minha pesquisa sobre casa, trabalho e escolaridade, numa região em que profundas transformações ajudaram a desarticular o mundo rural e desurbanizaram antigas vilas.

This article is an essay of interpretation in which an explanation in sought for the violence agaisnt children in our country. The starting - point is concerned with some results of my research on housing, work and schooling in an area where intense economical and cultural change has helped to disintegrate the rural world and de urbanize the old villages.
School, violence and child work in Brazil
Keywords: Violência; violência simbólica; dominação ideológica; trabalho infantil; moradia; ideologia e cultura; escolarização; ação pedagógica